Identification of land drought potential in Blora district using NDVI and NDWI methods - Lattu Arny; Baturohmah Habi; Erfina Adhitia; Saepudin Sudin; Sembiring Falentino (BIO Web of Conferences)
The plumbing system is an inseparable part of a multi-storey building. Drought is one of the routine disasters occurring in Indonesia. The occurrence of a prolonged disaster caused by the absence of countermeasures and good handling from the government. One of the causes of the drought is seasonal change. Blora district is one of the districts in Central Java that suffers severe drought other than other areas in Central Java which has two seasons: dry season and rainy season. The turn of the season resulted in a long drought in the Blora area. The purpose of this research is to identify the possibility of drought in Blora district by looking at several variables of drought index that is, vegetation index, wetness index and rainfall. To measure the vegetation index using NDVI (Normalized Difference Vegetation Index) method and for measure the wetness index using NDWI (Normalized Difference Water Index) method. The results of this research suggest that there is a relationship between vegetation index, wetness index and rainfall. When the value of wetness index increases then the vegetation index gets more solid. Like the data obtained in April 2016, the vegetation index in Blora District is -0.118 due to the dry season and the minimum rainfall that month.